Aire Downregulation Is Associated with Changes in the Posttranscriptional Control of Peripheral Tissue Antigens in Medullary Thymic Epithelial Cells - Oliveira, Ernna H.; Macedo, Claudia; Collares, Cristhianna V.; Freitas, Ana Carolina; Donate, Paula Barbim; Sakamoto-Hojo, Elza T.; Donadi, Eduardo A.; Passos, Geraldo A. (Frontiers in Immunology, 2016)
Autoimmune regulator (Aire) is a transcriptional regulator of peripheral tissue antigens (PTAs) and microRNAs (miRNAs) in medullary thymic epithelial cells (mTECs). In this study, we tested the hypothesis that Aire also played a role as an upstream posttranscriptional controller in these cells and that variation in its expression might be associated with changes in the interactions between miRNAs and the mRNAs encoding PTAs. We demonstrated that downregulation of Aire in vivo in the thymuses of BALB/c mice imbalanced the large-scale expression of these two RNA species and consequently their interactions. The expression profiles of a large set of mTEC miRNAs and mRNAs isolated from the thymuses of mice subjected (or not) to small-interfering (siRNA)-induced Aire gene knockdown revealed that 87 miRNAs and 4,558 mRNAs were differentially expressed. The reconstruction of the miRNA-mRNA interaction networks demonstrated that interactions between these RNAs were under Aire influence and therefore changed when this gene was downregulated. Prior to Aire knockdown, only members of the miR-let-7 family interacted with a set of PTA mRNAs. Under Aire knockdown conditions, a larger set of miRNA families and their members established this type of interaction. Notably, no previously described Aire-dependent PTA interacted with the miRNAs, indicating that these PTAs were somehow refractory. The miRNA-mRNA interactions were validated by calculating the minimal free energy of the pairings between the miRNA seed regions and the mRNA 3´ UTRs and within the cellular milieu using the luciferase reporter gene assay. These results suggest the existence of a link between transcriptional and posttranscriptional control because Aire downregulation alters the miRNA-mRNA network controlling PTAs in mTEC cells.